Successful maternal and fetal outcome of Guillain-Barre syndrome complicating pregnancy: a case report - Inamdar, Saunitra A.; Inamdar, Anil H.; Chaudhary, Richa; Subhedar, Vaidehi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Guillain-Barré syndrome rarely complicates pregnancy, incidence being 2/100000 population. We report a case of 23-year-old 2nd gravida who developed a progressive ascending paralysis during the second trimester of pregnancy. The worsening of the respiratory insufficiency required transfer to an intensive care unit but did not require artificial ventilation. Cerebrospinal fluid examination revealed albumin-cytological dissociation and repeated electrophysiological studies showed typical features of demyelinating neuropathy with conduction blocks. Biological investigations, especially CMV and campylobacter jejuni serologies, were all negative. Intravenous immunoglobulin infusions resulted in rapid improvement in the patient. This case raises the question of the relationship between the Guillain-Barré syndrome and pregnancy. The occurrence of the disease, as well as the rapid recovery in antenatal period could be consecutive to a partial failure of the maternal immunological tolerance toward the fetus.